2018
DOI: 10.18203/2319-2003.ijbcp20180657
|View full text |Cite
|
Sign up to set email alerts
|

Analgesic activity of Alpinia galanga extract in mice models and TNF-alpha receptor computational docking analysis on its leads with pharmacokinetics prediction

Abstract: Background: Alpinia galanga is an ayurvedic herb recognized and used across many traditional medicine systems for its analgesic and anti-inflammatory activity. The present study scientifically validates the potential anti nociceptive action of ethanolic extract of Alpinia galanga by chemical, neurogenic and inflammatory nociception model in mice followed by identification of potential lead compound by computational analysis.Methods: The assessment of anti nociceptive action is evaluated by Acetic acid induced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…The results indicated that a central mechanism of analgesic action was exhibited at 400 mg/kg and a peripheral mechanism of analgesic action was exhibited at 800 mg/kg. 25 In Swiss albino mice, Subhash et al 26 observed similar results. They further performed in silico studies using Schrodinger software.…”
Section: Analgesic Effectmentioning
confidence: 74%
“…The results indicated that a central mechanism of analgesic action was exhibited at 400 mg/kg and a peripheral mechanism of analgesic action was exhibited at 800 mg/kg. 25 In Swiss albino mice, Subhash et al 26 observed similar results. They further performed in silico studies using Schrodinger software.…”
Section: Analgesic Effectmentioning
confidence: 74%
“…Alpinia galanga 400mg/kg (71.70%) had comparable percentage inhibition of nociception to standard group indomethacin (88.71%) in the formalin-induced nociceptive mice model. Among 20 compounds screened for pharmacokinetic and druglike features, Galanal B had the binding free energy -56.664 when compared to control compound 2AZ5-56.000 (Subash et al, 2018). Ethanolic extract of Alpinia galanga rhizomes was given orally to experimental animals.…”
Section: Analgesic Activitymentioning
confidence: 99%
“…The control group received 0.1 mL/10 g of the vehicle. The reaction time (sec) of each group was noted with control and demonstrated as percent inhibition (16).…”
Section: Formalin Testsmentioning
confidence: 99%